Oral History Interview with Judith (Judy) Kruckman, March 2008 - Kruckman, Judith; Ramsey, Allen (My University, 2009)
Judith (Judy) Kruckman was the first women's athletic director at the university of Wisconsin--Eau Claire. This oral history interview was conducted by Allen Ramsey in support of his MA thesis research on Title IX and women's athletics at the University of Wisconsin--Eau Claire. His thesis, entitled "Continuing to Chip-Away" : How Title IX Changed Athletics at the University of Wisconsin-Eau Claire," is available in the University of Wisconsin--Eau Claire McIntyre Library.
Keywords: United States. Education Amendments of 1972. Title IX.; Women athletes --Wisconsin --Eau Claire --History.; College sports for women --Wisconsin --Eau Claire --History.; College sports --Wisconsin --Eau Claire --History.; Sex discrimination in sports --Wisconsin --Eau Claire --History.; University of Wisconsin--Eau Claire --Sports --History.